Innovative Development of the Food Industry in the Conditions of Sanctions and Import Substitution on the Basis of Public-Private Partnership - ROMANOVA, Julia Alexandrovna; BARKOVA, Natalya Yurievna; BORODINA, Olga Alexandrovna; SOLOVEVA, Marina Viktorovna; USTINOVA, Olga Evgenievna (Journal of Advanced Research in Law and Economics, 2020)
The research presents an attempt to elaborate an economic and organizational mechanism for innovative development of the food industry in the current conditions of sanctions and import substitution. The objective of this study is to provide a coherent methodology for developing an economic and organizational mechanism for innovative development of the food industry. In term of methods, the article is based on a system approach to assessing the current condition and identifying the issues related to innovative development of food industry enterprises, as well as a comparative analysis of management principles in the Russian food industry. The article provides an algorithm for effective cooperation between government and business – food industry enterprises – based on a wide range of methods of dialectical logic, binning, comparative and abstract-logical analysis. The results of this article can be used both in theory and practice regarding the development of tools for innovative development of food industry enterprises. Moreover, they can be used to advance scientific methods for improving competitiveness, investment attractiveness and economic resilience of food processing enterprises in the environment of increased innovative activity. Food industry enterprises show an increasing interest in innovative development of domestic agrarian producers as the main source of domestic primary products for own sustainable development. The proposed economic and organizational mechanism for the establishment and development of food industry enterprises in the framework of structural transformation management in the industry enables restructuring of the socio-economic situation in the food industry. The developed algorithm of a public-private partnership to attract investments to innovative development of Russian food processing enterprises aims to support and encourage export of food, enabling the government and regional authorities to promote rational use of investment potential of Russian regions, mitigation of investment risks and strengthening of food security in the country.